2010
DOI: 10.1016/j.seppur.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of azo dye Orange G in aqueous solutions by persulfate with ferrous ion

Abstract: 22This is the Pre-Published Version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(129 citation statements)
references
References 47 publications
8
107
0
Order By: Relevance
“…/PMS at neutral pH mineralized almost 90 % of the initial organic loading. Xu and Li (2010) also demonstrated that the Fe 2? /PS system could degrade azo dye orange G in aqueous solutions to a higher degree than the Fenton's reagent, which was beneficial to the mineralization of azo dyes.…”
Section: Effect Of Initial Phmentioning
confidence: 89%
“…/PMS at neutral pH mineralized almost 90 % of the initial organic loading. Xu and Li (2010) also demonstrated that the Fe 2? /PS system could degrade azo dye orange G in aqueous solutions to a higher degree than the Fenton's reagent, which was beneficial to the mineralization of azo dyes.…”
Section: Effect Of Initial Phmentioning
confidence: 89%
“…Furthermore, the addition of CS (1.2 g L −1 ) resulted in a sixtimes increase in degradation rate constants of COD and NH3. Xu et al have reported that by increasing the activator concentration (Fe 2+ ) from 1 to 4 mM, the degradation rate constant of Orange G increased from 0.04 to 0.12 min −1 [42]. …”
Section: Effect Of Reaction Time and Kinetic Studymentioning
confidence: 99%
“…Under acidic conditions, most iron ions existing in the process of electropersulfate are twovalent that result in a significant increase in efficiency by raising two-valent iron to three-valent iron ratio. Furthermore, at pH values above 4, solubility of ferric ions in solution decreased and these ions changed to colloidal form leading to a decrease in efficiency based on reaction 7 (Masomboon et al, 2010;Xu and Li, 2010). …”
Section: Effect Of Initial Phmentioning
confidence: 99%